PENDIDIKAN KETERAMPILAN PERDAMAIAN DAN RESOLUSI KONFLIK BAGI SISWA SMP DAN SMA SEKOLAH TUNAS DAUD DENPASAR, BALI - Pattinussa, Jhon Maxwell Yosua; Geraldine, Christa Olivia; Niyu, Niyu; Parani, Rizaldi; Pratikno, Roy Vincentius (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
Peace is both a need and a necessity for the Indonesian nation which has diversity. The difference that God has given to Indonesia is a gift that must be maintained and managed. Therefore, to avoid divisions and conflicts resulting from differences, it is only fitting that the Indonesian people are equipped with the knowledge and skills to manage this diversity. By focusing on the youth generation, as social agents in a peace society can be realized. Tunas Daud School, which was chosen to be a partner, houses students from various backgrounds and cultures. As a school built on Christian values ​​in a province where the majority adheres to Balinese Hinduism, the potential for conflict within the individual and group spheres is high, both in teaching and learning settings and in non-formal settings. In the process, a series of participatory interactive training activities were implemented for junior and senior high school students at this school. The team provides an understanding of peace and conflict resolution through nine training modules with a constructivist approach packed with various methods adapted for students in the age range of 12 to 18 years. The application of this skills training yielded very good overall results with the initial objectives being achieved. It also appears that there is an influence shown through the results of the pre-test and post-test as well as the evaluation results of the facilitator and participants.